PENGARUH KEPUTUSAN INVESTASI, KEBIJAKAN HUTANG, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN (Studi Kasus Pada Perusahaan Perbankan Konvensional yang Terdaftar di BEI tahun 2014-2016) - Siti Nur Anisah; Roni Malavia Mardani; M. Agus Salim (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACTFor three years beginning in the 2014-2016 period dividend fluctuated during the period. In this study, the authors will discuss Investment Decisions, Debt Policy and profitability that could affect dividend policy. The purpose of this study were (1) to determine the effect of investment decisions on dividend policy (2) to determine the effect of debt policy on dividend policy (3) to determine the effect on the profitability of the debt policy.This thesis research using this type of research that replication development, this study included Explanatory Research this study took samples from the population by using purposive sampling or judgment sampling method. By using two types of variables: Dependent variable (the dependent variable) and Independent Variables (independent variable). The results of this study are variable investment decisions (PER) of negative results significantly on dividend policy (DPR), the debt policy (DER) results were significant negative effect on dividend policy (DPR), profitability (EPS) of negative results is not significant to the dividend policy ( DPR).